Mobile money users' functionings and freedoms: Amartya Sen's capability approach - Otieno, Odoyo Collins; Liyala, Samuel (World Journal of Computer Application and Technology, 2018)
Over the last decade Amartya Sen’s Capability Approach has emerged as the leading alternative to standard economic frameworks for thinking about poverty, inequality and human development generally. Professor Sen has developed, refined and defended a framework that is directly concerned with human capability and freedom [1]. This framework as it looks at peoples’ freedoms and the means that enable them attain such freedoms, was found suitable for this study. This study therefore looked at mobile money users’ functioning and freedoms in both rural and urban settings. The framework was therefore established to be suitable in studying societal development that focuses on the people, the development being yearned for and the means to attain such development.
Keywords: Capability; Functioning; Freedom; Mobile Phone; Mobile Money; Services